Development of a Focused Library of Triazole‐Linked Privileged‐Structure‐Based Conjugates Leading to the Discovery of Novel Phenotypic Hits against Protozoan Parasitic Infections. (16th February 2018) - Uliassi, Elisa; Piazzi, Lorna; Belluti, Federica; Mazzanti, Andrea; Kaiser, Marcel; Brun, Reto; Moraes, Carolina B.; Freitas‐Junior, Lucio H.; Gul, Sheraz; Kuzikov, Maria; Ellinger, Bernhard; Borsari, Chiara; et al.
Abstract: Protozoan infections caused by Plasmodium, Leishmania, and Trypanosoma spp. contribute significantly to the burden of infectious diseases worldwide, causing severe morbidity and mortality. The inadequacy of available treatments calls for cost‐ and time‐effective drug discovery endeavors. To this end, we envisaged the triazole linkage of privileged structures as an effective drug design strategy to generate a focused library of high‐quality compounds. The versatility of this approach was combined with the feasibility of a phenotypic assay, integrated with early ADME‐tox profiling. Thus, an 18‐membered library was efficiently assembled via Huisgen cycloaddition of phenothiazine, biphenyl, and phenylpiperazine scaffolds. The resulting 18 compounds were then tested against seven parasite strains, and counter‐screened for selectivity against two mammalian cell lines. In parallel, h ERG and cytochrome P450 (CYP) inhibition, and mitochondrial toxicity were assessed. Remarkably, 10‐((1‐(3‐([1, 1′‐biphenyl]‐3‐yloxy)propyl)‐1 H ‐1, 2, 3‐triazol‐5‐yl)methyl)‐10 H ‐phenothiazine (7 ) and 10‐(3‐(1‐(3‐([1, 1′‐biphenyl]‐3‐yloxy)propyl)‐1 H ‐1, 2, 3‐triazol‐4‐yl)propyl)‐10 H ‐phenothiazine (12 ) showed respective IC50 values of 1.8 and 1.9 μg mL −1 against T. cruzi, together with optimal selectivity. In particular, compound 7 showed a promising ADME‐tox profile. Thus, hit 7 might be progressed as an antichagasic lead. Abstract : An 18‐membered library, rapidly and efficiently assembled by combining three privileged structures by catalyst‐ and solvent‐free Huisgen cycloaddition, was screened in parasite/mammalian cell‐based and early ADME‐tox assays. Notably, compound 7 emerged as an antichagasic phenotypic hit, with a good ADME‐tox profile. The simple and versatile triazole‐based conjugation strategy of privileged scaffolds might produce high‐quality antiparasitic conjugates.